Energetics of lanthanide cobalt perovskites: LnCoO3−δ (Ln = La, Nd, Sm, Gd). Issue 38 (14th October 2015) - Sahu, Sulata Kumari; Tanasescu, Speranta; Scherrer, Barbara; Marinescu, Cornelia; Navrotsky, Alexandra
<x xml:space="preserve">Abstract</x> The thermodynamic stability of lanthanide cobaltites is also a function of their existing oxygen non-stoichiometry.